THE DEVELOPMENTAL TOOLKIT: A PLAY-BASED LEARNING TOOL. (18th May 2018) - Young, Elizabeth; Jegathesan, Thivia; Ng, Stella; Mylopoulos, Maria; Minhas, Ripudaman S; Huber, Joelene; Zubairi, Mohammad
Abstract: BACKGROUND: Learning child development is complex. Recent paediatric and family medicine graduates reported feeling unprepared to identify and manage children with developmental and behavioural concerns (Comley et al 2008). As part of current developmental education at our centre, residents are trained to assess child development by integrating their pre-rotation knowledge about development with parental report and a general physical examination. This approach lacks hands-on training required to understand and learn the complexities of child development. To address this gap, our study team created the "Developmental Toolkit (Toolkit), " a non-standardized developmental teaching tool comprising specific toys and activities. OBJECTIVES: The primary objective of this study was to explore how the toolkit may influence the teaching and learning of child development. Through the lens of reflective practice, this study sought to also explore residents' learning of development in the context of a play-based toolkit. DESIGN/METHODS: Using a constructivist grounded theory approach, paediatric and family medicine residents from two academic centres were interviewed after they used the toolkit as part of their interactions. Physician supervisors were also interviewed to determine the use of the toolkit as a teaching tool. RESULTS: We recruited 10 residents to ensure saturation of data. Residents felt positively about their experience with the toolkit and its ease of use. They all agreed the toolkit enabled them to assess a child's developmental skills in a short period of time. One paediatric resident found it "really useful; it was a more objective way for me to see what skills and milestones they [the child] were at. I think it was quite useful to correlate it with what mom was saying." The residents' supervisors all felt the toolkit allowed residents to more critically consider a child's development and diagnosis in the context of the child's environment. Furthermore, through the lens of reflective practice, the use of the toolkit revealed additional competencies in child development. These included: 1) maintaining a positive mood with the child; 2) getting a sense of the parent's mood; 3) identifying when a child may have reached their limits during an interaction; and 4) critiquing previous assumptions about child development. CONCLUSION: The toolkit is an innovative tool that may enhance paediatric and family medicine residents' understanding of child development by enabling hands-on interactions and observations with children. Further exploration of how the toolkit may be enabling reflective practice and its implications on adaptive expertise need to be explored.